Crochet memory: affective Culture in biographical objects (Revista de Ensino em Artes, Moda e Design, 2021)
Any object can become a biographical object from the construction of the facts, the time andthe environment where it was inserted, in relation to human life. To understand the importanceof the affective relationships between human beings and their biographical objects is themain objective for the development of this work. Including, it seeks to identify the relevanceof affective relationships between people, by means of crocheting and its positive reflectionsfor the collective memory. This bibliographical, qualitative research, which, in an expositoryway, recreates a theoretical context. By social design methodological approaches, it usesstudies of articles and other scientific products. The affective relationships that are installedbetween human beings and these objects can also define the time, the place, the life historyof an individual or social group, in short, situate the territory. Crochet handicraft can beexecuted in a group and, consequently, by group dedication, it becomes a tradition. It wasobserved that crochet can be applied to any object, as long as the creative potential andthe research of materials are used. To meet the collective work, raw materials are soughtin the region. It drives the movement of revaluing the “handmade”. In this way, it becomespossible to insert the affective relationships with the objects, the places, and the entire lifehistory of an individual or social group.
Keywords: Affective memory; Biographical object; Crochet crafts